2017
DOI: 10.1186/s40425-017-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Viral based vaccine TG4010 induces broadening of specific immune response and improves outcome in advanced NSCLC

Abstract: BackgroundAdvanced non-small cell lung cancer patients receiving TG4010, a therapeutic viral vaccine encoding human Mucin 1 and interleukin-2 in addition to standard chemotherapy, displayed longer overall survival in comparison to that of patients treated with standard chemotherapy alone. Our study intended to establish the association between overall survival and vaccine-induced T cell responses against tumor associated antigens (TAA) targeted by the vaccine.MethodThe TIME trial was a placebo-controlled, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
(37 reference statements)
0
32
0
Order By: Relevance
“…In contrast, in lung cancer, a randomised study showed that the delivery of MUC1 in an MVA vaccine (TG4010) in the TIME study could lead to clinical benefit [ 163 ]. The study is further noteworthy as the authors showed convincingly that vaccination also induced T-cell reactivities against molecules that were not encoded in the vaccine [ 164 ]. This concept of ‘epitope spreading’ likely reflects the release of antigen from dying cancer cells, and if it can be reproduced in other trials, it would be an important feature of anti-cancer vaccination, both to be evaluated and as a path to broadening immune attack.…”
Section: Tumour-associated Antigens (Taas)mentioning
confidence: 99%
“…In contrast, in lung cancer, a randomised study showed that the delivery of MUC1 in an MVA vaccine (TG4010) in the TIME study could lead to clinical benefit [ 163 ]. The study is further noteworthy as the authors showed convincingly that vaccination also induced T-cell reactivities against molecules that were not encoded in the vaccine [ 164 ]. This concept of ‘epitope spreading’ likely reflects the release of antigen from dying cancer cells, and if it can be reproduced in other trials, it would be an important feature of anti-cancer vaccination, both to be evaluated and as a path to broadening immune attack.…”
Section: Tumour-associated Antigens (Taas)mentioning
confidence: 99%
“…MUC1-based clinical trials are currently ongoing, including retargeting human CD8 + and CD4 + T cells to tumor-associated MUC1 glycoforms ( 5 , 6 ). In addition, TG4010, a viral vaccine developed by Transgene SA, expresses full-length MUC1 and interleukin (IL)-2, and has demonstrated an association between overall survival and vaccine-induced T-cell responses ( 7 ). Lakshminarayanan et al ( 8 ) have also constructed a tumor vaccine by covalent attachment of a T-helper epitope and an aberrantly glycosylated MUC1 peptide, which induces immunoglobulin (Ig) G antibodies and cytotoxic T lymphocytes (CTLs) against MUC1.…”
Section: Introductionmentioning
confidence: 99%
“…Response to the viral vaccine was predicted by levels of natural killer (NK) cells and TG4010 plus chemotherapy improved progression-free survival compared with chemotherapy and placebo. Further studies on the patients and tumours from this trial indicate that TG4104 induces a broadening of the T-cell response to other tumour-associated antigens and the diversity of the T-cell response relates to response to therapy [ 22 ].…”
Section: Phase I/ii Trials Reported In the Literaturementioning
confidence: 99%